Pengembangan Sistem Informasi Our Book Berbasis Website untuk Menyimpan File Materi (Current Research in Education: Conference Series Journal, 2022)
In the current era, information technology is developing very rapidly. Almost all daily activities use information technology, including in the field of education. So it is not surprising that currently the learning material provided to students is in the form of files. Many material files make it difficult for students to store and classify the material they have. Therefore, we conducted research with the aim of solving problems in accommodating various lecture material files. This study uses the SDLC method with a waterfall model. The waterfall model is used to design and develop the information system to be created. Researchers conducted a survey of 70 Indonesian students and the results obtained by 60% of students admitted that they still had difficulty managing material files and the most widely used online storage media was Google Drive at 52.3%. From the results of the research and the problems previously described. Researchers provide a solution, namely a new innovation in the form of our website-based Book Information System. Our book is a web-based platform that is able to store and organize material files in various forms such as photos, pdf, documents and others into one platform such as a material bank.